The associations between mental health symptoms and cognitive and social functioning among school-aged children from diverse migration backgrounds - Kirsi Peltonen; Sanni Aalto; Oskari Lahtinen; Joosu Soosalu; Samuli Kangaslampi; Jonathan Hall; Gustaf Gredebäck (BMC Psychology, 2026)
Abstract Background Mental health symptoms may be linked to cognitive and social functioning in school-aged children, but less is known about whether these associations differ across migration-background groups. Methods We examined cognitive, social, and mental health measures among 227 pupils in grades 4–6 in Finland (mean age 10.9 years (SD = 1.0), 51% girls) using cross-sectional design. Native-born children represented 47% of the total sample, first-generation immigrant children without refugee background 40%, and first-generation refugee-background children 13%. Group differences were examined using ANOVA models, and associations between trauma-related and depressive symptoms and cognitive/social outcomes were examined using moderated regression models. Results Groups did not differ significantly in trauma exposure, trauma symptoms, depressive symptoms, or measured social functioning. Across the sample, trauma-related and depressive symptoms were associated with several social-functioning outcomes, while associations with cognitive outcomes were more mixed and, in some cases, differed by migration-background group. Refugee-background children showed lower visuospatial short-term memory than native-born and immigrant-background children. Conclusions Findings suggest that mental health symptoms are linked to school-relevant cognitive and social functioning across diverse pupil groups, and that some cognitive associations may vary by migration background. Results should be interpreted as tentative given the cross-sectional design, small refugee-background subgroup, and measurement constraints. Trial Registration The study was preregistered at OSF (https//doi.org/10.17605/OSF.IO/T6SXM). Registration date Sep 2, 2024.